A Critical Analysis of the Influence of Teachers’ Quality on the Achievement of English Language Learners in Akwa Ibom State (Eurasian Journal of Learning and Academic Teaching, 2022)
The study sought to find out how teachers’ quality influence the academic achievement of the students in English language. Correlational survey design was adopted for the study. The study was carried out in selected public secondary schools in Uyo Local Government Area of Akwa Ibom State. The population of this study comprised senior secondary two students in Uyo Local Government Area. There are 14 public secondary schools in Uyo Local Government Area and the estimated population of SS2 students was 3162. Simple random sampling technique was used to select eight public secondary schools where 303 SS 2 students were randomly selected for the study. The instrument used in this study for data collection was a questionnaire titled "Students Factors Questionnaire (SFQ)". The instrument was vetted and content validated by the researcher’s supervisor and two lecturers who are experts in language education in the University of Uyo to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.97, and this was high enough to justify the use of the instrument. The data were analyzed using t-test and Pearson Product Moment Correlation statistics analysis. The test for significance was done at 0.05 alpha levels. From the findings and discussions of this study, it could be concluded that the higher the quality of a teacher (in respect of training, qualification, character and teaching method); the higher the academic achievement of a student. Also that teaching of English Language requires a competent, trained and qualified English teacher. Finally, by implication, a good professional teacher in English Language will produce sound and reliable students in English Language. But an unqualified and non-professional teacher in English will mar academic excellence in students of English Language. Therefore, one of the recommendations was to revise the existing teachers training programs with respect to admission criteria, curriculum, teaching practice and measurement and evaluation process. Proper training of teacher may strengthen the causal-relationship between the various qualities of teachers and academic achievement